Topics in Cryptology - CT-RSA 2022: Cryptographers' Track at the RSA Conference 2022, Virtual Event, March 1-2, 2022, Proceedings - Galbraith, Steven D (Lecture Notes in Computer Science, 2022)
This book constitutes the refereed proceedings of the Cryptographer's Track at the RSA Conference 2022, CT-RSA 2022, held in San Francisco, CA, USA, in February 2022.*The 24 full papers presented in this volume were carefully reviewed and selected from 87 submissions.CT-RSA is the track devoted to scientific papers on cryptography, public-key to symmetric-key cryptography and from crypto-graphic protocols to primitives and their implementation security.*The conference was held as a hybrid event.